Darunavir/Cobicistat/Emtricitabine/Tenofovir Alafenamide Versus Dolutegravir/Abacavir/Lamivudine in Antiretroviral-Naive Adults (SYMTRI): A Multicenter Randomized Open-Label Study (PReEC/RIS-57). (25th November 2021) - Podzamczer, D; Micán, R; Tiraboschi, J; Portilla, J; Domingo, P; Llibre, J M; Ribera, E; Vivancos, M J; Morano, L; Masiá, M; Gómez, C; Fanjul, F; et al.
Abstract: Background: Darunavir/cobicistat/emtricitabine/tenofovir alafenamide (D/C/F/TAF) is the reference for combination therapy based on protease inhibitors due to its efficacy, tolerability, and convenience. Head-to-head randomized comparisons between D/C/F/TAF and combination therapy based on integrase inhibitors in antiretroviral-naive patients are lacking. Methods: Adult (>18 years old) human immunodeficiency virus-infected antiretroviral-naive patients (HLA-B∗5701 negative and hepatitis B virus negative), with viral load (VL) ≥500 c/mL, were centrally randomized to initiate D/C/F/TAF or dolutegravir/abacavir/lamivudine (DTG/3TC/ABC) after stratifying by VL and CD4 count. Clinical and analytical assessments were performed at weeks 0, 4, 12, 24, and 48. The primary endpoint was VL <50 c/mL at week 48 in the intention-to-treat (ITT)-exposed population (US Food and Drug Administration snapshot analysis, 10% noninferiority margin). Results: Between September 2018 and 2019, 316 patients were randomized and 306 patients were included in the ITT-exposed analysis (151 D/C/F/TAF and 155 DTG/3TC/ABC). Almost all (94%) participants were male and their median age was 35 years. Forty percent had a baseline VL >100 000 copies/mL, and 13% had <200 CD4 cells/μL. Median weight was 73 kg and median body mass index was 24 kg/m 2 . At 48 weeks, 79% (D/C/F/TAF) versus 82% (DTG/3TC/ABC) had VL <50 c/mL (difference, −2.4%; 95% confidence interval [CI], −11.3 to 6.6). Eight percent versus four percent experienced virologic failure but no resistance-associated mutations emerged. Four percent versus six percent had drug discontinuation due to adverse events. In the per-protocol analysis, 94% versus 96% of patients had VL <50 c/mL (difference, −2%; 95% CI, −8.1 to 3.5). There were no differences in CD4 cell count or weight changes. Conclusions: We could not demonstrate the noninferiority of D/C/F/TAF relative to DTG/ABC/3TC as initial antiretroviral therapy, although both regimens were similarly well tolerated. Abstract : D/C/F/TAF is the reference for combination therapy based on protease inhibitors but has not been compared with regimens containing integrase inhibitors as initial ART. We could not demonstrate D/C/F/TAF noninferiority relative to DTG/ABC/3TC, although both regimens were similarly well tolerated.